Excitation Energy Transfer/Migration between Tris(8-hydroxyquinoline) Aluminum and Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] in Chloroform - Bisht H.; Rawat G.; Jit S.; Mishra H. (My University, 2025)
Excitation energy transfer/migration between fluorescent electron transport molecule tris(8-hydroxyquinoline) aluminum (donor) and fluorescent hole transport polymer poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (acceptor) were studied in chloroform solution at room temperature using steady-state and time-domain fluorescence measurements. The blend of this pair is widely used in the fabrication of organic light-emitting diode. The considerable overlap integral between the emission spectrum of donor and absorption spectrum of acceptor indicates high donor-acceptor interaction, and the effective enhancement of the acceptor fluorescence along with a decrease in fluorescence intensity of donor by exciting the donor states characterized the excitation energy transfer between them. Relatively faster decay of donor in the presence of a higher concentration of acceptor followed the Förster kind of long-range fluorescence resonance energy transfer, which is illustrated by the agreement in the values of the energy transfer parameters observed from the fluorescence decay analysis and the values calculated from the spectral overlap. However, at lower acceptor concentrations, the excitation energy migration and diffusion/intrachain interaction influence the kinetics, resulting in a significant difference in the observed and calculated value of the energy transfer parameters. The influence of intrachain and interchain interactions during nonradiative excitation energy transfer is confirmed by the donor and acceptor decay dynamics on increasing acceptor concentration in donor-acceptor solution. No evidence of excimer formation is noticed in the donor-acceptor solution. Copyright © 2020 American Chemical Society.